INFLUENCE OF REVERSE LOGISTICS PRACTICES ON ENHANCING COMPETITIVENESS IN MANUFACTURING FIRMS IN KENYA: A CASE OF EAST AFRICAN BREWERIES LTD - Mbovu, Daniel Kilonzo; Mburu, Dr. David Kiarie (International Journal of Supply Chain Management, 2018)
Purpose: The purpose of this study was to establish the influence of reverse logistics practices on enhancing competitiveness in manufacturing firms in Kenya. Methodology: The study population was 240 staff in the department of logistics Procurement and Finance at East Africa Breweries Limited. A questionnaire with both open ended and closed questions was used to collect raw data from the respondents. The simple random was carried out and primary data was through the use of questionnaires. The secondary data was obtained from published documents such as journals, periodicals, magazines and reports to supplement the primary data. A pilot study was conducted to test the reliability and validity of the data collection instrument. The data was analyzed with the help of SPSS. The study adopted a regression analysis at 5% level of significance to determine strength and direction of the relationship of the variables under study. Descriptive statistics were used to analyze the data in frequency distributions and percentages presented herein in tables of frequency distribution, percentages, bar graphs and pie-charts. The study adopted a multiple regression analysis so as to establish the relationship of independent variables and dependent variables. The study applied SPSS compute the measurements of the multiple regression analysis. Results: The findings revealed that there exists a relationship between independent variables and dependent variable with a correlation coefficient of 0.789. The coefficient of determination is between zero and one. The data showed that the high R square is 0.622. It showed that the independent variables in the study were able to explain 62.20% variation in the competitiveness of the manufacturing firms while the remaining 37.80% is explained by the variables or other aspects outside the model. This implies that these variables are very significant and they therefore need to be considered in any effort to boost competitiveness of the manufacturing firms. Unique contribution to theory, practice and policy: Based on the findings, the study recommended that the manufacturing firms should collect used products to the repair workshops from customers to make new products. The firms should train their employees on repair and refurbishing of the products to meet customers' expectations. The manufacturing firms should repackage the product and resend the same product to the market. There is need to enhance distributor returns the product for repackaging to the manufacturing firm and thus the firm is able to save transport costs. Through repackaging the manufacturing firm is able to portray high levels of responsibility and care for the end users. The study recommended that the manufacturing firms' returns used products and packaging to suppliers for recycling. There is need for awareness creation to the public about recycling of the products, have a well documented and implemented recycling policy. The study recommended that the manufacturing firm material handling, storage locations should be where the shipping of the products to minimize picking time. The storage locations will enable the firm to achieve competitive advantage by consistently reviewing sales data as the items are stored close to the shipping area. The firm warehouse layout should be in such that minimize travel time between picking locations. There is need to adopt material handling technologies such as hand-held reader, pick to light and voice recognition technology to enhance competitiveness of the firms. Keywords: Reverse logistics, practices, competitiveness, manufacturing firms